Importin subunit beta‐1 mediates ERK5 nuclear translocation, and its inhibition synergizes with ERK5 kinase inhibitors in reducing cancer cell proliferation - Zoe Lombardi; Lucia Gardini; Anatolii V. Kashchuk; Alessio Menconi; Matteo Lulli; Ignazia Tusa; Alessandro Tubita; Luisa Maresca; Barbara Stecca; Marco Capitanio; Elisabetta Rovida (Molecular Oncology)
The mitogen‐activated protein kinase (MAPK) extracellular signal‐regulated kinase 5 (ERK5) is emerging as a promising target in cancer. Indeed, alterations of the MEK5/ERK5 pathway are present in many types of cancer, including melanoma. One of the key events in MAPK signalling is MAPK nuclear translocation and its subsequent regulation of gene expression. Likewise, the effects of ERK5 in supporting cancer cell proliferation have been linked to its nuclear localization. Despite many processes regulating ERK5 nuclear translocation having been determined, the nuclear transporters involved have not yet been identified. Here, we investigated the role of importin subunit alpha (α importin) and importin subunit beta‐1 (importin β1) in ERK5 nuclear shuttling to identify additional targets for cancer treatment. Either importin β1 knockdown or the α/β1 importin inhibitor ivermectin reduced the nuclear amount of overexpressed and endogenous ERK5 in HEK293T and A375 melanoma cells, respectively. These results were confirmed in single‐molecule microscopy in HeLa cells. Moreover, immunofluorescence analysis showed that ivermectin impairs epidermal growth factor (EGF)‐induced ERK5 nuclear shuttling in HeLa cells. Both co‐immunoprecipitation experiments and proximity ligation assay provided evidence that ERK5 and importin β1 interact and that this interaction is further induced by EGF administration and prevented by ivermectin treatment. The combination of ivermectin and the ERK5 inhibitor AX15836 synergistically reduced cell viability and colony formation ability in A375 and HeLa cells and was more effective than single treatments in preventing the growth of A375 and HeLa spheroids. The increased reduction of cell viability upon the same combination was also observed in patient‐derived metastatic melanoma cells. The combination of ivermectin and ERK5 inhibitors other than AX15836 provided similar effects on cell viability. The identification of importin β1 as the nuclear transporter of ERK5 may be exploited for additional ERK5‐inhibiting strategies for cancer therapy.